Opuntia cladode powders inhibit adipogenesis in 3 T3-F442A adipocytes and a high-fat-diet rat model by modifying metabolic parameters and favouring faecal fat excretion - Cécile Héliès-Toussaint; Edwin Fouché; Nathalie Naud; Florence Blas-; Maria del Socorro Santos-Diaz; Anne Nègre-Salvayre; Ana Paulina Barba de la Rosa; Françoise Guéraud (BMC, 2020)
Abstract Background Obesity is a major public health concern worldwide. A sedentary life and a nutritional transition to processed foods and high-calorie diets are contributing factors to obesity. The demand for nutraceutical foods, such as herbal weight-loss products, which offer the potential to counteract obesity, has consequently increased. We hypothesised that Opuntia cladodes consumption could assist weight management in an obesity prevention context. Methods This study was designed to explore the anti-adipogenic effects of lyophilised Opuntia cladode powders (OCP) in an in vitro cellular model for adipocyte differentiation and an in vivo high-fat-diet (HFD)-induced obesity rat model. Two OCP were tested, one from wild species O. streptacantha and the second from the most known species O. ficus-indica. Results Pre-adipocytes 3 T3-F442A were treated by OCP during the differentiation process by insulin. OCP treatment impaired the differentiation in adipocytes, as supported by the decreased triglyceride content and a low glucose uptake, which remained comparable to that observed in undifferentiated controls, suggesting that an anti-adipogenic effect was exerted by OCP. Sprague-Dawley rats were fed with a normal or HFD, supplemented or not with OCP for 8 weeks. OCP treatment slightly reduced body weight gain, liver and abdominal fat weights, improved some obesity-related metabolic parameters and increased triglyceride excretion in the faeces. Taken together, these results showed that OCP might contribute to reduce adipogenesis and fat storage in a HFD context, notably by promoting the faecal excretion of fats. Conclusions Opuntia cladodes may be used as a dietary supplement or potential therapeutic agent in diet-based therapies for weight management to prevent obesity. Graphical abstract